2020
DOI: 10.1039/d0sc02009e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structural heterogeneity upon the microviscosity of ionic liquids

Abstract: The behaviour of two molecular rotors have been studied in various ionic liquids. Time resolved fluorescence shows a complex relationship between the bulk viscosity of the ionic liquid and microstructure of solvent around each molecular rotor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…A very characteristic example of that is the melting point of a very commonly studied IL, [C 2 C 1 im][BF 4 ], for which the available data vary from 5.8 to 16 C. 136 There are also many studies of reaction kinetics, which is another domain where ML methods could be useful, 137 that show that common impurities, such as moisture or unreacted starting materials can signicantly affect the results. 138 In order for results to be reproducible, the ILs have to be either ultrapure (<0.1% of impurity levels) 139 or the level of purity has to be clearly stated in each work. This has become more common in works published in the last few years, but there are minimal purity data from earlier IL research, which unfortunately makes their use very limited without re-testing the results.…”
Section: Consistencymentioning
confidence: 99%
“…A very characteristic example of that is the melting point of a very commonly studied IL, [C 2 C 1 im][BF 4 ], for which the available data vary from 5.8 to 16 C. 136 There are also many studies of reaction kinetics, which is another domain where ML methods could be useful, 137 that show that common impurities, such as moisture or unreacted starting materials can signicantly affect the results. 138 In order for results to be reproducible, the ILs have to be either ultrapure (<0.1% of impurity levels) 139 or the level of purity has to be clearly stated in each work. This has become more common in works published in the last few years, but there are minimal purity data from earlier IL research, which unfortunately makes their use very limited without re-testing the results.…”
Section: Consistencymentioning
confidence: 99%
“…Although the [NTf 2 ] À anion is commonly thought of as a weakly coordinating anion, it does have several hydrogen bond acceptor groups and we have previously observed that [NTf 2 ] À can form multiple hydrogen bonds with olefinic CH protons in the Cy3 molecular dye, leading to surprisingly large structural deformations in a supposedly planar cation. 74 In [NRC 2 C 1 C 1 im][NTf 2 ], multiple hydrogen bonds are formed between the C 4/5 -H protons and oxygen atoms of the [NTf 2 ] À anion, leading to two symmetry-independent [NTf 2 ] À anions in the asymmetric unit (Fig. 11).…”
Section: Analysis Of Hydrogen Bondingmentioning
confidence: 99%
“…The viscosity and ionic conductivity of those RAILs can be affected by the temperature-dependent microstructural and dynamic heterogeneities of the ILs. 44,45 For our [CzC 4 ImC 1 ][TFSI] and [C 4 VC 7 ][TFSI] 2 systems, however, no data suggest the presence of the such phase-separated structures in these RAILs.…”
Section: Resultsmentioning
confidence: 74%
“…In these species, electrostatic, van der Waals, hydrogen bonding, dipole–dipole, and π–π interactions all play important roles in the formation of microstructures, leading to unanticipated transport features and functionalities. 44,45 Understanding these strong and weak interactions will provide new insights into the transport properties and functionalities in ILs. In this regard, it is noteworthy that the effect of CT interaction in ILs on the physicochemical and electrochemical properties is presently unclear.…”
Section: Introductionmentioning
confidence: 99%